Heterogeneity in the Paraventricular Thalamus: The Traffic Light of Motivated Behaviors - McGinty, Jacqueline F.; Otis, James M. (Frontiers in Behavioral Neuroscience, 2020)
The paraventricular thalamic nucleus (PVT) is highly interconnected with brain areas that control reward-seeking behavior. Despite this known connectivity, broad manipulations of PVT often lead to mixed, and even opposing, behavioral effects, clouding our understanding of how PVT precisely contributes to reward processing. Although the function of PVT in influencing reward-seeking is poorly understood, recent studies show that forebrain and hypothalamic inputs to, and nucleus accumbens and amygdalar outputs from, PVT are strongly implicated in PVT responses to conditioned and appetitive or aversive stimuli that determine whether an animal will approach or avoid specific rewards. These studies, which have used an array of chemogenetic, optogenetic, and calcium imaging technologies, have shown that activity in PVT input and output circuits is highly heterogeneous, with mixed activity patterns that contribute to behavior in highly distinct manners. Thus, it is important to perform experiments in precisely defined cell types to elucidate how the PVT network contributes to reward-seeking behaviors. In this review, we describe the complex heterogeneity within PVT circuitry that appears to influence the decision to seek or avoid a reward and point out gaps in our understanding that should be investigated in future studies.